MEROKOK DALAM PERSPEKTIF MUHAMMADIYAH DAN NAHDHATUL ULAMA - Muhammad Ihsan (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2017)
Smoking is an activity that has become part of human life in differene partsof the world. However smoking is a thing that can be said to be relativelynew, because cigarettes have not been known at the time of Prophet SAW.Because it is a new one, it’s not suprising it is appears a variety of differentopinions in a non legislation, both ulama in person or religious organizationwhich is often used as a reference for the general public. Muhammadiyahthrought the council of tarjih have established to consider unlawful thesmoking, while Nahdatul Ulama established that the smoking law merelyimproper. The differences of opinion certainly is something to be examinedfuther. Moreover, both organization are the largest organization inIndonesia and has fanaticism its self. So that whatever be the decicionwould have passable